Phytochemical Characterization and Antioxidant Evaluation of Withania somnifera: Implications for Traditional Therapeutics - Preetam; Tiwari, Vijeyta (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was conducted to evaluate some in-vitro phytochemical and antioxidative properties of Withania somnifera root extract for further accessing its potentiality as a hepatoprotective agent in in-vivo model. Qualitative tests for presence of various active principles like alkaloid, phenol, glycoside, saponin, tannin and resins were performed in an aqua methanolic extract of Withania somnifera root powder. Further, Withania somnifera root extract was also evaluated for its in-vitro antioxidant properties by DPPH and ABTS level measurements by standard methods. The results showed the presence of alkaloids, glycosides, phenols, resins, saponins, proteins and flavonoids in the extract sample. In the case of antioxidant markers, Withania somnifera root extract exhibited potent radicals scavenging property in a concentration dependent manner. From these results, it is concluded that Withania somnifera root extract possess good antioxidant potential. Thus Withania somnifera could be a good choice of agent to evaluate its hepatoprotective potential in animals.